Data for the paper "Stochastic multi-objective optimisation of the cure process of thick laminates" - Tifkitsis, Konstantinos; Struzziero, Giacomo; Skordos, Alexandros A. (Cranfield University, 2018)
Surrogate_model_validation.xlsx includes the data corresponding to the comparison between FE and surrogate model (responses surfaces, PDF of model error, stochastic simulation)-Uncertainty_quantification_results.xlsx includes the results of uncertainty quantification of convection coefficient and tool temperature.-Stochastic_optimisation_results.xlsx includes the stochastic and deterministic Pareto points of stochastic and deterministic optimisation respectively.-Sensitivity_analysis_results.xlsx includes the data corresponding to the sensitivity analysis of standard and optimal profiles.-flat_panel_15.6mm.dat : Marc input corresponding to Cure model of this study-usub.f: contains all the subroutines for material properties and boundary conditions
Keywords: 'Cure process'; 'Uncertainty quantification'; 'Stochastic optimisation'; 'Kriging'; 'Aerospace Engineering'; 'Aerospace Materials'; 'Optimisation'; 'Stochastic Analysis and Modelling'